Academics as decision makers: what style do they adopt? - Zizah Che Senik; Ridzuan Md Sham; Nik Mu’tasim Nik Abdul Rahman; Rosmah Mat Isa; Md Daud Ismail; Mohd Dzul Azzwan Mohd Nor; Noor Azuan Hashim; Ahmad Khairy Ahmad Domil (Penerbit Universiti Kebangsaan Malaysia, 2012)
Many studies have focused on the decision-making styles (DMS) of managers, but very few have studied the DMS among academicians. Using the Rowe Decision Style Inventory, this study investigates the DMS of the academics in a public university in Malaysia. The objectives are to identify the common styles adopted by the academics and to determine their dominant styles in relation to their gender, age, faculty, qualifications, and years of service. This study employed a quantitative-questionnaire design that was distributed to 163 academics during an in-house training program. Four types of DMS—directive, analytical, conceptual, and behavioural styles—were identified with regard to gender, age, faculty, qualifications, and years of service. The results revealed that while the majority of the respondents have more than one dominant DMS, the conceptual and analytical styles predominate. Additionally, empirical evidence of variations in the types of DMS across demographic characteristics was found. These findings provide important implications for academics in making the most effective decisions within their profession